PENGARUH CURRENT RATIO DAN DEBT TO ASSETS RATIO TERHADAP RETURN ON ASSETS PADA PERUSAHAAN HOTEL, RESTORAN DAN PARIWISATA YANG TERDAFTAR DI BEI - Batubara, Hade Chandra; Amirah, Afifah Amirah; Astuti, Diana Dwi (Catholic University Musi Charitas, 2020)
This study aims to determine the effect of Current Ratio (CR) and Debt to Assets Ratio (DAR) partially and simultaneously on Return On Assets (ROA) in hotel, restaurant, and tourism companies listed on the Indonesia Stock Exchange (BEI). The sample used in this study amounted to 8 out of 10 companies in the hotel, restaurant, and tourism sub-sector listed on the IDX in the period 2014 - 2017. The sample selection used a purposive sampling technique, in which the researcher set specific provisions tailored to the research objectives. The data analysis technique used is multiple linear regression, classical assumption test, t-test, F test, and coefficient of determination. Based on the simultaneous test, it was found that the variables Current Ratio and Debt to Assets Ratio had a significant effect on Return On Assets in the hotel, restaurant, and tourism sub-sector companies listed on the IDX.